Development of energy conversion and lightning strike protection simulation for photovoltaic-wind turbine on grid - Satria, Habib; Mungkin, Moranain; Dayana, Indri; Ramdan, Dadan; Maizana, Dina; Syafii, Syafii (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Photovoltaic (PV) installations and wind turbines that are installed on the rooftops of buildings need to be protected because the layout is in a high position and there is a risk of being struck by lightning. Therefore, a more effective protection system is designed to anticipate electronic damage and fire on all materials in the distribution network, especially the addition of PV and wind turbine installations on building roofs. The purpose of this study is to simulate a lightning protection system on the distribution network and the results of on-grid PV energy conversion using electrical transient analyzer program (ETAP) software. Feeder relay delay times and cascade coordination patterns between outgoing and incoming relays do not overlap. the delay time of the relay working on the feeder is 0.31 s and the coordination pattern of the outgoing relay and incoming relay does not touch each other, so the delay time for the incoming relay is 2.73 s. Then testing the results of PV energy conversion connected to the grid using MATLAB Simulink monitoring obtained data reaching 1.600 Wp at peak power with sun conditions parallel to the PV installation layout.